If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2t + 2x = 8 Solving -2t + 2x = 8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2x' to each side of the equation. -2t + 2x + -2x = 8 + -2x Combine like terms: 2x + -2x = 0 -2t + 0 = 8 + -2x -2t = 8 + -2x Divide each side by '-2'. t = -4 + x Simplifying t = -4 + x
| 3x^5+17x^4+10x^3=0 | | .30(x+40)+.30x=21 | | 25y+52x-15z-7(6y+3x+4z)+10y-9x-12z= | | -2p=-9.76 | | 4x+2=1x+11 | | 16-4x=8+3x-6 | | y^2dx+dy=0 | | 3--1/2=m | | 3X-40+2X-20=180 | | -475=r+-226 | | 40-3p=39+1 | | 6(v-1)-6=-6(-3v+5)-2v | | F-313=94 | | 5x+21+20x+34= | | 16x+y=19 | | -3x^2+14x=8 | | p+27=4*p-15 | | 15x=21+4-35 | | 12x+14+20x+34=180 | | 2(8x-6)+3x+8=-175 | | X+20+X-10=180 | | 18+18+18=f | | 4+2n-2=6n+4-2n | | t-n=t+ax | | W+68=14 | | 2[x-(4x)+3]=2x+2 | | R+53=93 | | X+20=X-10 | | 5x-7+3(4x-9)=204 | | D+-384=-969 | | 6x-3-3x= | | N=33*(-15) |